Math, asked by krishna544843, 1 year ago

12m3+6m2-6m factorise ......​

Answers

Answered by SomyaRaman
28

12m^3+6m^2-6m

=6m(2m^2+m-1)

=6m{2m^2+(2-1)m-1}

=6m{2m^2+2m-m-1}

=6m{2m(m+1)-1(m+1)}

=6m{(m+1)(2m-1)}

=6m(m+1)(2m-1)

Answered by Asgardian
8

Answer:

The factors of given expression are 6m(m+1)(2m-1)

Step-by-step explanation:

Here the given expression is: 12m^3+6m^2-6m  

Let suppose the given expression is equal to A so we can re write given expression as below:

A=12m^3+6m^2-6m

take 6m common from RHS. we get,

A=6m(2m^2+m-1)

Now factor expression on RHS, we get,

A=6m(2m(m+1)-1(m+1))

A=6m(m+1)(2m-1)\\

hence factors of given expression are 6m(m+1)(2m-1)

Similar questions